Few-layer large Ti3C2Tx sheets exfoliated by NaHF2 and applied to the sodium-ion battery. Issue 15 (10th March 2021) - Zhao, Yan; Zhang, Meng; Yan, Hong; Feng, Yu; Zhang, Xinyu; Guo, Ruijie
Abstract : The first time to use NaHF2 aqueous solution to synthesize Ti3 C2 T x, making Na + ions intercalated between Ti3 C2 T x layers, which has excellent thermal and structural stability and is a high-performance anode for sodium-ion battery. Abstract : Since the original discovery, MXene can be synthesized by wet-chemical etching from the MAX phase. To avoid the shortcomings of the previous etchant, NaHF2 aqueous solution was used for the selective removal of Al from Ti3 AlC2, while intercalating Na + between layers. The d -spacing of the resulting accordion-like Ti3 C2 T x is up to 12.35 Å; the by-product Na3 AlF6 can be removed by H2 SO4, and the product yield can reach about 85%. After a short time of centrifugation and sonication, few-layer (10–20 layers) Ti3 C2 T x sheets in a large lateral size (3–4 μm) can be prepared, with high conductivity up to 2.3 × 10 5 S m −1 . Ti3 C2 T x can be stably dispersed in water and organic solvents for at least 96 h, and has excellent anti-thermal-oxidation ability. As the anode for sodium ion batteries, the Ti3 C2 T x electrode delivers a high reversible capacity of 70 mA h g −1 after 900 cycles at a current density of 1 A g −1 with an extremely low-capacity decay rate. From 900 to 1000 cycles, the capacity can even be increased to 130 mA h g −1, and the Coulomb efficiency is close to 100%, showing that MXene can provide a stable structure for the Na + cycle.